RITUAL NGANGKID PADA UPACARA NELUBULANIN MASSAL DI DESA ADAT KEROBOKAN, KECAMATAN KUTA UTARA, KABUPATEN BADUNG - Supadmini, Ni Kadek; I Made Suastika; Relin D.E (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
This article descriptively describes the principle of unification of the ngangkid ritual at the mass nelubulanin ceremony in the Kerobokan Traditional Village includes The system for implementing the ngangkid ritual at mass nelubulanin ceremonies includes :Historical factors of the ngangkid ritual which cannot be separated from magical and mystical experiences, Continuing ancestral heritage, namely an identity that must be maintained and inherited, Community support, which is one of the rituals that gets support from the community; and Community belief as the embodiment of atmanastuti. The system for implementing the ngangkid ritual at mass nelubulanin ceremonies includes : The literary sources used are Catur Veda Samhita, Adi Parwa Mahabharata, Tutur Gong Besi, and Tutur Kahuripan Lan Kamoksan. Facilities and offerings in the form of jukung-jukungan, axis, banten pengangkidan,banten pengresikan pejati, Daksina gede, holy, serodan, sweetening. Participants are 170 participants. The leader is a Pandita. The procession begins with pengaksama and pangastawa, nganyud jukung-jukungan, pamuspaan, murwadaksina. Time and place of implementation, namely not taking pasah and titi buwuk. The implications and meaning of Hindu theology for the ngangkid ritual are The implications of tattwa include widhi tatwa and samsara tattwa, Moral implications, namely forming the personality of the person being held at the ceremony, The implications of awareness in society, namely awareness of wisdom, Socio-cultural implications, namely mutual cooperation, Economic implications, namely the existence of an economic turnaround, Innovation Implications, namely a new breakthrough carried out en mass.